PELAKSANAAN KODE ETIK HAKIM PERSPEKTIF SIYASAH SYAR’IYYAH - Ramadhani, Ahmad Fathur; Sohrah (Prodi Hukum Tata Negara (Siyasah Syariyyah) Fakultas Syariah dan Hukum UIN Alauddin Makassar, 2024)
This research aims to analyze the implementation of the judge's code of ethics from the perspective of siyasah syar'iyyah. The problem of this research is the number of judges who violate the judge's code of ethics. This research uses a type of qualitative field research with a normative (Syar'i) approach and a juridical approach. Data collection methods were carried out by means of observation, interviews and documentation. The results of this research show that judges are state judicial officials who are authorized by law to adjudicate. The emergence of a discourse on the professional code of ethics for judges arises because it departs from the reality of law enforcers (especially judges) who ignore moral values. Even though we already have a professional code of ethics for judges as a moral standard, it turns out that it has not had a positive impact, because in implementing the code of ethics for judges there are still many professional judges who violate this code of ethics, as has happened at the Makassar District Court.